Multidimensional Comparative Analysis of the Competitiveness of the European Union Countries' Economies - Katarzyna Cheba; Katarzyna Szopik-Depczynska (Institute of Economic Research (IER), 2017)
The basic question we ask is, whether it is possible to talk in today's globalizing world about the uniform of the competitiveness of the economies. Posing such questions is particularly important in the case of such political and economic structures such as the European Union. The strategic developmental objectives of the EU include the aspiration to harmonious development of all of its members but it is very difficult task. The competitiveness of the economies is now one of the most frequently discussed topics. It is very difficult to precisely define the notion of competitiveness unambiguously, particularly in terms of international competitiveness of economies. The competitiveness of economies can be discussed both in the context of : a) international competitive capacity, b) international current competitiveness or c) international competitive standing of national economy. In this work, due to the context of the conducted research (international comparisons of the EU countries' economies) the competitiveness of international economies will be considered in terms of international competitive capacity with regard to investment attractiveness of a country. In addition to the problems associated with defining this concept they are also important dilemmas associated with the measurement of the competitiveness. In the performed comparative analyses of European economies the research results presented within reports of 'Global Competitiveness Index' will be used. The aim of the work is multidimensional comparative analysis of the competitiveness of the European Union countries' economies. In the work to study the spatial differentiation of the EU countries' economies in the context of their competitiveness, the taxonomic measure of development based on median vector Weber has been used. As a result the classification and the typological groups of the EU countries obtained by means of the taxonomic measure of development calculated on the basis of the characteristics of their competitiveness arises.
Keywords: C38; O11; P36; 330; competitiveness of the economies; multidimensional comparative analysis; the European Union